Analisis Kinerja Guru Berdasarkan Kepemimpinan Kepala Sekolah, Motivasi dan Kompetensi Guru (Studi pada SMP Negeri Se-Kecamatan Samalanga Kabupaten Bireuen) - Husin, Idris; Kamaruddin, Kamaruddin (Singkite Journal, 2024)
This research aims to analyze teacher performance based on the Principal's Leadership, teacher motivation and competence. With associative quantitative methods and multiple regression analysis techniques. This research was conducted on State Middle School teachers in Samalanga District, Bireuen Regency. The research results show that: 1) Partially the principal's leadership, teacher motivation and competence have a positive influence on teacher performance. 2) Together the principal's leadership, teacher motivation and competence contribute 43.3% to teacher performance.